2021
DOI: 10.1111/acem.14318
|View full text |Cite
|
Sign up to set email alerts
|

Nonfatal firearm injuries: Utilization and expenditures for children pre‐ and postinjury

Abstract: Objective: Firearm injuries are one of the leading preventable causes of morbidity and mortality among children. Limited information exists about the impact of nonfatal firearm injuries on utilization and expenditures. Our objective was to compare health care encounters and expenditures 1 year before and 1 year following a nonfatal firearm injury. Methods:This was a retrospective cohort study of children 0 to 18 years with ICD-9/ ICD-10 diagnosis codes for firearm injury (excluding nonpowder) in the emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Our findings also demonstrate older victims were more likely to be connected to mental health services post injury, whereas victims 15–19 years of age were less likely to receive a mental health diagnosis compared to victims 20–24 years of age. Pulcini and colleagues observed a similar decrease post injury mental health visits among youth but reasons for the decrease in mental health utilization post injury remains unclear ( Pulcini et al, 2021 ). Such age disparities may speak to access to mental health services and parental decision making regarding when and if youth are connected to mental health services ( Neufeld et al, 2021 ), as parents report not knowing when their child may need such services ( Bringewatt and Gershoff, 2010 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our findings also demonstrate older victims were more likely to be connected to mental health services post injury, whereas victims 15–19 years of age were less likely to receive a mental health diagnosis compared to victims 20–24 years of age. Pulcini and colleagues observed a similar decrease post injury mental health visits among youth but reasons for the decrease in mental health utilization post injury remains unclear ( Pulcini et al, 2021 ). Such age disparities may speak to access to mental health services and parental decision making regarding when and if youth are connected to mental health services ( Neufeld et al, 2021 ), as parents report not knowing when their child may need such services ( Bringewatt and Gershoff, 2010 ).…”
Section: Discussionmentioning
confidence: 97%
“…Similar changes in mental health utilization were found in a study of pediatric nonfatal firearm victims using Medicaid MarketScan claims over six years. For example, youth with lower preinjury utilization had more mental health utilization post injury and youth with higher preinjury utilization had less mental health utilization post injury ( Pulcini et al, 2021 , Retraction. Acad Emerg Med., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated low utilization of MH services and largely unmet MH needs in trauma patients. [22][23][24] Violent injuries are often associated with greater risk of MH symptoms and recurrent injury compared with nonviolent injuries. 11,12 Oddo et al 25 recently reported that ∼25% of children had a newly diagnosed MH disorder after a nonfatal firearm injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings, based on health care utilization claims, likely underestimate the prevalence of MH disorders. Previous research has indicated low utilization of MH services and largely unmet MH needs in trauma patients 22–24…”
Section: Discussionmentioning
confidence: 99%
“…As a group of researchers dedicated to investigating firearm injuries among children and adolescents, we recently published in Academic Emergency Medicine and then selfretracted work that inadvertently included nonpowder firearm injuries in our analysis. 7 This error was due to a failure to closely examine…”
Section: Introductionmentioning
confidence: 99%